2010
DOI: 10.1088/0256-307x/27/11/114211
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photonic Quasicrystal Fiber with Broadband Large Negative Dispersion

Abstract: A broadband highly dispersive fiber based on a dual-concentric-core photonic quasicrystal fiber (PQF) is designed for chromatic dispersion compensation. The fiber is composed of pure silica background and air-holes without doping. The fundamental supermode has a large negative dispersion value of about −9600 ps•nm −1 •km −1 over an optical communication band around 1550 nm and a full width at half maximum (FWHM) of 40 nm. By adjusting the structural parameters, a dispersion of −2250 ps•nm −1 •km −1 around 1550… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Structures quasi-periodic of the type quasicrystals are unique structures that have long range in the direction of propagation, but without periodicity. Recently, studies have found that quasi-periodic structures can originate an important phenomena and properties which are not observed in periodic structures [3], [4]. For example, introduction of 12-fold symmetry in quasicrystals through air holes in a dielectric matrix with low refractive index creates photonic gaps, i.e., frequency bands in which the light propagation is totally prohibited, except for the case of some PCFs settings that allow the propagation of light through the Photonic Band Gap (PBG) [4], [15].…”
Section: Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Structures quasi-periodic of the type quasicrystals are unique structures that have long range in the direction of propagation, but without periodicity. Recently, studies have found that quasi-periodic structures can originate an important phenomena and properties which are not observed in periodic structures [3], [4]. For example, introduction of 12-fold symmetry in quasicrystals through air holes in a dielectric matrix with low refractive index creates photonic gaps, i.e., frequency bands in which the light propagation is totally prohibited, except for the case of some PCFs settings that allow the propagation of light through the Photonic Band Gap (PBG) [4], [15].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In addition, the size of the holes can be adjusted from the temperature control. [4], [5]. However, Photonics Quasicrystal Fibers (PQCF) has attracted the attention of the scientific community, due to its ability to present symmetry in higher orders, as for example symmetry with twelve replicates (twelve-fold).…”
mentioning
confidence: 99%
“…and the basic matrix is shown in Figure 1 (b). In addition, the introduction of symmetries with an aperiodic array of air holes, in a dielectric matrix with low refractive index produces photonic band gaps, i.e., disallowed bands of frequency in which the light propagation is totally banned [3]. In the limit, for small wavelengths (Λ/λ → ∞), the light is forced to remain only in the region of defects due to the total internal reflection phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pulse compressors based on these novel fibers turn out to be a hopeful method for fiber-format pulse shortening. With such fibers, a high nonlinearity is combined with the tailored dispersion to allow the pulse compression to the pulse widths as short as few femtoseconds [5][6][7][8][9][10][11][12].In this work, we design a novel PQF which provides the hitherto mentioned desired optical properties.…”
Section: Introductionmentioning
confidence: 99%